Peningkatan Ketepatan Kode Diagnosis ICD-10 melalui Pelatihan, Pendampingan, dan Quality Control Rekam Medis di Rumah Sakit - Deno Harmanto; Anggia Budiarti; Khodijah (Gayaku Publisher, 2025)
The accuracy of diagnosis coding using the International Classification of Diseases, 10th Revision (ICD-10) is an essential component of medical record quality, health data validity, and healthcare financing systems. However, in practice, various coding errors are still found due to limited staff competence, incomplete clinical documentation, and the lack of continuous evaluation. This community service activity aimed to improve the accuracy of ICD-10 diagnosis coding through training, mentoring, and medical record quality control in hospitals. The program was implemented in stages, including theoretical training and case-based coding exercises, direct mentoring in the medical record unit, and periodic medical record audits as a form of quality assurance. Evaluation was conducted on 100 medical record files before and after the intervention. The results showed that the accuracy of primary diagnosis coding increased from 68% to 90%, while the accuracy of secondary diagnosis coding increased from 60% to 85%. Errors in the use of the fourth character of ICD-10 decreased from 32% to 10%, and the use of overly general codes declined from 28% to 8%. In addition, the completeness of clinical documentation improved from 70% to 92%. This activity proved effective in enhancing the competence of medical record officers, improving the quality of diagnosis coding, and supporting the improvement of health data quality and hospital services. Therefore, continuous training, regular mentoring, and routine medical record quality audits are recommended as sustainable strategies to maintain the accuracy of ICD-10 coding.